Government Recommendations for the Effective Implementation of QuickCommerce Policy to Transform the E-Commerce Sector - Muhammad Younus; Tunjung Sulaksono; Suranto Suranto (Engineering, MAthematics and Computer Science Journal (EMACS), 2023)
This paper aims to determine the guideline regarding the Initiative of the Government to transform the E-commerce industry of the country and take it to a new level of QuickCommerce. The Researchers who are working on the research in this field of work are using ‘Qualitative Research.’ This research material was taken from social media, Online Media, Websites, and Articles, and then it is displayed in descriptive format. This paper indicates that making this guideline will ensure the improvement needed in the E-commerce Market and make it ready for the successful implementation of QuickCommerce in the country. Several steps need to be followed to create and successfully implement QuickCommerce—first, the analysis and determining the significant challenges are present currently, which is pushing back the smooth implementation. Second, the selection of the way forward for the implementation of it and deciding the critical indicators required for it. Finally, then proposing the solution based on the analysis. This study is limited to the extent to which the problem is clearly defined, then suggests the solution with its working flow, and lastly, what advantage it will provide to solve the problem that the current E-commerce market is facing.